2012
DOI: 10.1177/0269215512442915
|View full text |Cite
|
Sign up to set email alerts
|

Afferent stimulation provided by glove electrode during task-specific arm exercise following stroke

Abstract: This study describes a unique SES delivery system via glove electrode that enabled delivery of SES during home-based arm task practice in stroke survivors. Task practice with concurrent SES did not demonstrate significantly better effects than task practice with sham stimulation, however there was a trend for greater improvement in one activity measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(73 citation statements)
references
References 58 publications
(107 reference statements)
1
72
0
Order By: Relevance
“…666,728,729,[731][732][733] A variety of interventions have been the focus of ≥1 studies but have not yet been shown to be consistently beneficial for upper limb motor rehabilitation. These include somatosensory stimulation [734][735][736][737][738] and noninvasive brain stimulation (transcranial magnetic stimulation or tDCS) in combination with upper extremity exercise therapy, [739][740][741][742][743][744][745][746] interventions targeting motor apraxia, 458 and manual therapy approaches such as stretching, passive exercise, and mobilization, 748 although these approaches are a routine part of practice for individuals with more severely affected upper extremities to prevent contractures and to manage spasticity.…”
Section: Iib Bmentioning
confidence: 99%
“…666,728,729,[731][732][733] A variety of interventions have been the focus of ≥1 studies but have not yet been shown to be consistently beneficial for upper limb motor rehabilitation. These include somatosensory stimulation [734][735][736][737][738] and noninvasive brain stimulation (transcranial magnetic stimulation or tDCS) in combination with upper extremity exercise therapy, [739][740][741][742][743][744][745][746] interventions targeting motor apraxia, 458 and manual therapy approaches such as stretching, passive exercise, and mobilization, 748 although these approaches are a routine part of practice for individuals with more severely affected upper extremities to prevent contractures and to manage spasticity.…”
Section: Iib Bmentioning
confidence: 99%
“…Previous studies [12][13][14] have found mixed results with regard to SS specific changes in arm function. McDonnell et al 13 found no between-group differences in ARAT change after median nerve stimulation and TST.…”
Section: Functional Improvementsmentioning
confidence: 93%
“…In chronic stroke survivors, improvements in pinch strength 8 , functional task performance 9 and motor training 10,11 have been observed after a single session. Several studies have examined the cumulative effect of SS and motor training in chronic stroke [12][13][14] . McDonnell et al 13 found small improvements in hand dexterity, which were not accompanied by changes in corticospinal excitability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations